2022
DOI: 10.14573/altex.2109011
|View full text |Cite
|
Sign up to set email alerts
|

In vitro models of the canine digestive tract as an alternative to in vivo assays: Advances and current challenges

Abstract: Dogs occupy a full place in the family and their well-being is of paramount importance to their owners. Digestion, a complex process involving physicochemical, mechanical, and microbial parameters, plays a central in maintaining animals healthy. As in vivo studies in dogs are more and more restricted by ethical, regulatory, societal, and cost reasons, an alternative option resides in the use of in vitro models simulating the different parts of the canine gastrointestinal tract. This review paper first introduc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(12 citation statements)
references
References 171 publications
(276 reference statements)
1
7
0
Order By: Relevance
“…Authors established that the large intestinal transit time represents 40, 55, and 70% of total transit time for small, medium, and large dogs, respectively. Applied to the mean total transit times established from our literature review for each dog size (in total 23 studies (Deschamps et al 2022b ), we calculated average large intestinal transit times of 10, 18, and 30 h for small, medium, and large dogs, respectively. Those estimations were fully in line with in vivo data from studies which estimated this digestive parameter in various dog sizes (Bruce et al 1999 ; Hernot et al 2006 ; Boillat et al 2010 ; Lidbury et al 2012 ; Gazzola et al 2017 ; Koziolek et al 2019 ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Authors established that the large intestinal transit time represents 40, 55, and 70% of total transit time for small, medium, and large dogs, respectively. Applied to the mean total transit times established from our literature review for each dog size (in total 23 studies (Deschamps et al 2022b ), we calculated average large intestinal transit times of 10, 18, and 30 h for small, medium, and large dogs, respectively. Those estimations were fully in line with in vivo data from studies which estimated this digestive parameter in various dog sizes (Bruce et al 1999 ; Hernot et al 2006 ; Boillat et al 2010 ; Lidbury et al 2012 ; Gazzola et al 2017 ; Koziolek et al 2019 ).…”
Section: Resultsmentioning
confidence: 99%
“…In accordance with the “3Rs” rules (adapted from Russel and Burch 1959 ) which prone the reduction of animal use and the development of in vitro alternative strategies, the main objective of this study was to develop and validate through in vitro-in vivo comparisons the first model reproducing the canine colonic ecosystem adapted to three dog sizes, the CANIM-ARCOL. This was achieved thanks to a wide literature review (150 publications) we previously performed on canine colonic physicochemical (pH and transit time), nutritional (composition of simulated ileal effluents including nutrients and bile acids), and microbial (gut microbes’ composition and functionalities) parameters (Deschamps et al 2022b ). Up to now, most of the systems (8 out of 10) developed to reproduce the canine colonic environment are static batch models (Sunvold et al 1995 ; Tzortzis et al 2004 ; Bosch et al 2008 ; Cutrignelli et al 2009 ; Panasevich et al 2013 ; Vierbaum et al 2019 ; Duysburgh et al 2020 ; Van den Abbeele et al 2020 ; Oba et al 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…Finally, all these data concerning the effect of dog size on their digestive physiology can be helpful for the development of new food or veterinary products at the individual level, in accordance with a personalization step intended by petfood and pharma companies. In full accordance with the 3R rules (aiming to reduce animal experiments), such in vivo data also provide key information necessary to develop and validate in vitro gut models adapted to each dog sizes for in-depth mechanistic studies on dog digestive physiology 128 .…”
Section: Discussion and General Conclusionmentioning
confidence: 99%
“…The applicant provided many publications at this respect. Some of these publications review the use of in vitro methods and their usefulness to study the digestion in dogs (Harmon, 2007 ; De Godoy et al, 2016 ; Deschamps et al., 2022 ); others provide data on in vitro studies only (Van Zelst et al, 2015 ; Lee et al, 2017 ; Kim et al., 2021 ) or do not allow for a full comparison of the results with those obtained in vivo (Gajda et al., 2005 ); a couple describe methods that may not be comparable to the one described by Boisen in 2007 (Smeets‐Peeters et al, 1999 ; Bosch et al, 2016 ); and some were developed from Boisen's or can be considered comparable but do not provide validation of in vivo reference values at pre‐caecal level (Dufour‐Etienne et al, 1992 ; Tonglet et al, 2001 ; Hervera et al, 2007 ; Hervera et al, 2009 ; Hooda et al, 2012 ; Biagi et al, 2016 ; Penazzi et al, 2021 ). Some of the latter showed good correlation between the digestibility coefficients in vitro and in vivo (faecal data); the conditions of the studies and diets evaluated may play a major role in the correlations observed.…”
Section: Assessmentmentioning
confidence: 99%